Augmented Reality dalam Media Pembelajaran Tata Cara Berwudhu dan Tayamum - Ayu Latifah; Ridwan Setiawan; Arfan Muharam (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2021)
In Islamic religious education, especially in the procedures for purification where ablution and tayammum are very important because these are mandatory requirements in carrying out prayers. Often the procedures for ablution and tayammum are not understood properly and correctly because the process of delivering the material is still using conventional methods with media in the form of books that are less interesting and interactive. The purpose of making an application for purification procedures using Augmented Reality as a visual learning medium that can be understood by users, namely early childhood and emphasizes the importance of ablution and tayammum in Islam. The Multimedia Development Life Cycle method is used in making this application with six stages carried out starting from concept generation, design, material collection, manufacture, alpha and beta testing and the last stage in the form of distribution of applications that have been built. The results of this study can be used as an alternative learning media with interactive features using augmented reality which discusses how to perform ablution and tayammum properly and correctly in worship according to Islamic law.